Analisis Kata Harpazontes Berdasarkan Yudas 1:23 dan Implementasinya Terhadap Penginjilan - Pattinaja, Aska Aprilano; Kiamani, Andris; Manurung, Well Therfine Renward (STT Pelita Dunia, 2025)
Outreach is a term that is very often heard in the evangelistic movement. The term is generally translated as trying to win lost souls. Interestingly, Jude 1:23 is often used in the context of soul winning with an emphasis on the word harpazontes. The purpose of this study is to put the right perspective on the word harpazontes and its implications from an evangelistic point of view. By using a qualitative method with a hermeneutic exegesis study to conduct a theological study of the word harpazontes, this article finds three results of the analysis of the word harpazontes, namely: first, the context of this word refers to the act of seizing souls who have repented only to become shaky and go back astray; second, the context of this word is different from the word